Investigating the Effectiveness of Fourier Transform Infrared Spectroscopy (FTIR) as an Antifraud Approach for Modified Epoxy Asphalt Mixes in Developing Countries - Ngezahayo, Esdras; Eskandari Torbaghan, Mehran; Metje, Nicole; Burrow, Michael; Ghataora, Gurmel S.; Desalegn, Yitagesu (Sustainability, 2023)
The road surfacing material is continuously exposed to both traffic and climate stresses, including extreme temperatures and heavy rainfalls. Subsequently, most road defects start from the surface and potentially develop into road structural damage. Appropriate road maintenance schemes are necessary to ensure the surface remains functionable. On the other hand, these maintenance schemes would be uneconomical without the use of durable and climate-resilient materials for road surfacing. This is vital in low-income countries (LICs), where the burdens of road maintenance are economically unbearable. In this regard, long-life epoxy-modified asphalt offers an opportunity to achieve durable and climate-resilient pavement surfacing. However, epoxy is an expensive material that may be subject to fraud, leading to poor quality of the surfacing mixture and the resulting road infrastructure. In order to prevent fraud and ensure the quality of epoxy bitumen mixtures for road surfacing, Fourier transform infrared spectroscopy (FTIR) was used to characterise mixes of epoxy-modified bitumen and trace the content of epoxy. The findings showed that the epoxy content used in the preparation of mixes agreed with the epoxy content traced using FTIR. The mean difference between the two quantities was approximately ±1.0% with a correlation coefficient R2 > 0.9. Therefore, FTIR can efficiently provide an antifraud method for modified epoxy asphalt mixes at the plant level to help achieve sustainable pavements.